A Programming Tool for the Development of Parallel Computer Vision and Image Processing Algorithms and Applications - Bruno, Odemir Martinez; Costa, Luciano da Fontoura (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2001)
This article presents the development, implementation, and applications of the CVMP parallel programming tool for image processing and computer vision. Running on Borland Delphi and C++ Builder, this simple and easy-to-use tool incorporates visual programming and object oriented capabilities, having already allowed a series of applications and results, which are also outlined.